Model Pembelajaran Tematik Ditinjau Dari Prestasi Belajar Matematika Siswa SD - Artati Iriana; Ari Setiawan (Jurnal Akademik Pendidikan Matematika, 2022)
Problem in this research was wheteher the use of learning model o thematics effective in learning math topic of counting operation of multiplication and subtraction at grade III of SD Negeri 1 Kambowa. Objective in this research was to find out the effectiveness of learning model of thematic in learning math topic of counting operation of multiplication and subtraction. This research used quantitative approach with quasi experimental design. Population in this research was all student at grade III of SD Negeri 1 Kambowa which consisted of two classes IIIA and IIIB with the number of students was 58. Data in this research were obtained using test of math subject. Result of the research obtained: 1) mean score of learning achievement of math at experimental class before research conducted was 68,96; 2) mean score of learning math at experimental class after being taught by thematic learning model as 86,03; 3) mean score of learning math at control class before research conducted was 65,17; 4) mean score of learning math at control class after being taught by direct learning model was 77. Based on those mean score of learning math and considering the inferential result by using t-test, they indicated that learning model of thematic is more effective than direct learning on topic of counting operation of multiplication and subtraction at grade III students of SD Negeri 1 Kambowa